Antioxidants and antibacterial properties of extracts from leaves and stem of pink flower Impatiens walleriana - Tan, Suat Hian; Sin, Phin Yin; Mohd Hairul, Ab. Rahim; Ros Azlinawati, Ramli; Putri Shareen, Rosman (AIP Publishing, 2024)
Impatiens walleriana is a vibrant and flowering plant sources cherished for its antioxidants and antimicrobial properties. This research aimed to evaluate the impact of three different drying treatments (microwave drying, oven drying, and air drying) on the antioxidant compounds of leaves and stems of pink flower I. walleriana. Besides, antibacterial efficacy of leaves extract against Gram-positive and Gram-negative bacteria were also evaluated. Microwave-dried leaves extract exhibited high phenolic (6.358±0.18 mg GAE/100g), flavonoid (0.528±0.005 mg QAE/100g) and caffeoylquinic acid contents (0.988±0.012 mg CQCA/100g), followed by oven-dried and air dried. Stem extracts of I. walleriana showed relatively less phenolic compound as compared to leaves extract probably due to the plant’s defense strategy against environmental stress. Besides, the leaves extract was chosen for antibacterial activity using Kirby-Bauer disc-diffusion method. The results revealed that I. walleriana able to suppress growth of both Gram-positive and Gram-negative bacteria. Nevertheless, I. walleriana had stronger inhibitory effect against Escherichia coli while least inhibitory effect against Pseudomonas aeruginosa, with inhibition zone of 6.6 mm and 1 mm, respectively. The antibacterial effect of I. walleriana also found superior to streptomycin especially against Gram-negative bacteria. The antibacterial effect of I. walleriana against E. coli was found to be two times stronger than the synthetic antibiotics. Hence, this indicates that I. walleriana had a good potential as an alternative source of antioxidant and antimicrobial and replacing the synthetic additives in current market.